PENGARUH DISIPLIN KERJA, KOMITMEN ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN UNIT OPERATION PADA PT TELKOM AKSES MATARAM - Muhammad Fathurrahman; Santi Nururly; Mukmin Suryatni (Master of Management, Mataram University, 2023)
The aim of this research was to determine the effect of Work Discipline, Organizational Commitment and Work Environment on the Performance of Unit Operations Employees at PT. Telkom Access Mataram. The type of research applied is associative research. The technical analysis uses Multiple Linear Regression. The method used is the census method in which the respondents are employees of the operation unit of PT. Telkom Access Mataram with a total of 34 people. From this study, the results of the analysis stated that: 1. Work discipline has a positive and significant influence on the performance of employees at the operation unit of PT. Telkom Access Mataram. 2. Organizational commitment has a positive but not significant effect on the performance of employees at the operation unit of PT. Telkom Access Mataram. 3. The work environment has a positive and significant influence on the performance of employees at the operation unit of PT. Telkom Access Mataram.